Developing E-Learning Materials for a Blended Learning Environment: A Case Study - Lutfiani, Firda; Sakdiya, Halimatus; Safitri, Aisah Maharani Adinda (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2024)
Using a case study approach, this research investigates how e-learning can be a strategic solution to increase the flexibility and effectiveness of learning in the digital era, especially in blended learning environments, which combine online and face-to-face learning methods. The purpose of this research is to create flexible and interactive e-learning materials that can be used for blended learning. This research shows that well-designed or created e-learning materials can increase student participation, material comprehension, and learning independence. In addition, this research also found the main challenges in applying e-learning to blended learning, such as technology readiness, teacher support, and student participation. The results of this research are expected to provide practical guidance for educators and students.